Liver abscess after endoscopic sleeve gastroplasty: A case report - Vincenzo Cirimele; Giulia D'Amone; Daniele Vertulli; Giuseppe Spagnolo; Matteo Pileri; Edoardo Montanari; Eliodoro Faiella; Bruno Beomonte Zobel (Radiology Case Reports, 2023)
Endoscopic sleeve gastroplasty is a minimally invasive procedure for the treatment of obesity. The procedure is generally safe and well-tolerated, but major adverse events occur in up to 3% of patients. Perigastric abscess is a potential complication caused by postprocedural gastric leak. To the best of our knowledge, no cases of hepatic abscess (HA) following endoscopic sleeve gastroplasty have been reported, while HA is a well-known complication of laparoscopic sleeve gastrectomy. We report the case of a patient who developed a liver abscess 2 weeks after endoscopic sleeve gastroplasty. The patient improved with administration of intravenous antibiotics and endoscopic drainage.